2020
DOI: 10.1177/0033294120961524
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychosocial Outcomes and Fanship in K-Pop Fans: A Social Identity Theory Perspective

Abstract: Korean pop culture (K-Pop) has spread its influence outside of Korea to a worldwide fan audience. The present study investigated the self-categorised K-Pop fandom characteristics that predicted higher levels of K-Pop fanship, and subsequent psychosocial outcomes. Social identity theory was applied as a theoretical framework. In total, 1477 K-Pop fans from 92 predominantly Western countries fully completed an extensive online survey measuring fanship, fandom and psychosocial outcomes (happiness, self-esteem and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 28 publications
2
22
0
3
Order By: Relevance
“…In the context of pop culture, the idol or celebrity usually refers to pop star, sports hero, etc. Within the past 20 years, fandom, which refers to the community of fans who are attached to each other with common ingroup identity, has been evolving substantially with the development of social media platform (Laffan, 2021).…”
Section: Literature Review and Theoretical Foundation Idol Worship An...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of pop culture, the idol or celebrity usually refers to pop star, sports hero, etc. Within the past 20 years, fandom, which refers to the community of fans who are attached to each other with common ingroup identity, has been evolving substantially with the development of social media platform (Laffan, 2021).…”
Section: Literature Review and Theoretical Foundation Idol Worship An...mentioning
confidence: 99%
“…Previous studies on celebrity worship and idol worship within the context of pop culture discussed the intrinsic nature of this phenomenon (Till, 2010;Gleason et al, 2017); examined behavioral and psychological features of online and offline fans (Williams and Ho, 2016;Kunert, 2021), especially the psychological well-being (Brooks, 2021), psychiatric symptoms (e.g., depression, anxiety, difficulties in integration of experiences in various life domains, and maladaptive daydreaming; Somer et al, 2017;Zsila et al, 2018), and pathological, addictive, or deviant behavior (McCutcheon et al, 2002;Zsila et al, 2019) associated with entertainment idols within a clinical context (Maltby et al, 2006;Sheridan et al, 2007); developed multiple measurement tools (Maltby et al, 2006;Cheung and Yue, 2011); identified the correlates, antecedents and outcomes of celebrity worship (Ang and Chan, 2018;McCutcheon et al, 2021), including demographics (Gleason et al, 2017), personality (Maltby and Day, 2017), social, behavioral, and psychological factors (Brooks, 2021;Laffan, 2021); explored the operating mechanisms of fandom and fan culture within the field of pop culture and social media platforms (Van den Bulck et al, 2016;Yin, 2020), the routine practices of "algorithmic culture" (Alaimo and Kallinikos, 2017;Fung, 2019;Livingstone, 2019), the sense of duty and obligation as commitment to the community and the idol (Zhang and Fung, 2017), as well as the interaction and co-evolution among multiple actors including the idol, pop industry, fans, and social media platform (Giles, 2002;Yan and Yang, 2021). However, few of them have focused on the final stage of idol worship, including the breakup and recovery process.…”
Section: Literature Review and Theoretical Foundation Idol Worship An...mentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, other research showed how fanaticism actually provides a positive influence on fans' well-being, which in turn manifest in their demeanor (Laffan, 2020;Lozano et al, 2020). However, fans' image and identity are also strongly affected by media narratives and how the general public emotional response to them (Oliver & Bartsch, 2011;Vinney et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…This reluctance would be affecting fans' psychosocial well-being. Several studies revealed that there were positive aspects, where media fiction narratives or idols could provide, from idolizing or fanaticism (Laffan, 2020;Lozano Delmar et al, 2020). These acts of reluctance would certainly be creating a negative impact on fans' psychological and social life.…”
Section: Introductionmentioning
confidence: 99%